Windows on the workplace : technology, jobs, and the organization of office work - Greenbaum, Joan (New York, 2005)
"In this eye-opening book, Joan Greenbaum tells the story of changes in management policies, work organization, and the design of office information systems from the 1950s to the present. She describes the impact of new technologies on the organization of working life with a keen awareness of the social forces that seek to benefit from them, showing how the process is driven by the needs of capitalist profit and control over the workforce rather than greater efficiency. "